1997
DOI: 10.1200/jco.1997.15.1.246
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of fluorouracil and low-dose leucovorin given for 6 months as postoperative adjuvant therapy for colon cancer.

Abstract: These results indicate that intensive-course 5FU plus low-dose leucovorin is effective in preventing tumor relapse and improving survival in patients with high-risk colon cancer. These benefits were seen with only six cycles of treatment, using low-dose leucovorin in combination with 5FU on a schedule convenient for outpatient administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
212
2
13

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 535 publications
(230 citation statements)
references
References 11 publications
3
212
2
13
Order By: Relevance
“…Unfortunately, steady-state plasma 5FU levels do not correlate with toxicity (Jodrell et al, 2001) and hence pharmacokinetic monitoring is not used to identify patients who are at increased risk of toxicity (Tebbutt et al, 2000). In randomised controlled trials, dose reductions are common after the first two cycles and 15 -30% of patients fail to complete chemotherapy (Wolmark et al, 1993;O'Connell et al, 1997;Poplin et al, 2005). The relationship between systemic exposure and treatment efficacy has not been demonstrated, however, and can only be ascertained by conducting prospective randomised studies that compare a targeted dose adjustment to a fixed dose (Milano et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, steady-state plasma 5FU levels do not correlate with toxicity (Jodrell et al, 2001) and hence pharmacokinetic monitoring is not used to identify patients who are at increased risk of toxicity (Tebbutt et al, 2000). In randomised controlled trials, dose reductions are common after the first two cycles and 15 -30% of patients fail to complete chemotherapy (Wolmark et al, 1993;O'Connell et al, 1997;Poplin et al, 2005). The relationship between systemic exposure and treatment efficacy has not been demonstrated, however, and can only be ascertained by conducting prospective randomised studies that compare a targeted dose adjustment to a fixed dose (Milano et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In einer Studie, in denen Patienten mit Stadium-II-Tumoren und Hochrisikocharakteristika eine kleine Untergruppe darstellten, konnte kein Benefit einer adjuvanten Chemotherapie gegenüber der alleinigen operativen Therapie gezeigt werden [879]. Im Gegensatz dazu stellten in der MOSAIC-Studie Patienten mit Stadium-II-Tumoren mit einem T4-Tumor, einer Tumorperforation, einem Ileus, einem schlecht differenzierten Tumor, einer Blutgefäßinvasion und/oder weniger als 10 untersuchten Lymphknoten eine Hochrisikopopulation dar, bei der die postoperative adjuvante FOLFOX4-Chemotherapie im Vergleich zu einer 5FU/FS-Chemotherapie zu einer nicht signifikanten Verbesserung des 10-Jahre-krankheitsfreien-Überlebens um 3,7 % Prozentpunkte führte.…”
Section: Level Of Evidence 1aunclassified
“…from the results of numerous large-scale randomised trials and from the pooled analysis of clinical trials (Wolmark et al, 1993; International Multicentre Pooled Analysis of Colon Cancer Trials (IMPACT) investigators, 1995;O'Connell et al, 1997). In 2004, results from the Multicenter International Study of Oxaliplatin/5-FU/Leucovorin in the Adjuvant Treatment of Colon Cancer (MOSAIC) trial demonstrated that combination chemotherapy with 5-FU/LV (de Gramont regimen) plus oxaliplatin was significantly superior to 5-FU/LV alone (André et al, 2004).…”
mentioning
confidence: 99%